Sulfonic acid (SO3H) functionalized two-dimensional MoS2 nanosheets for electrocatalytic hydrogen generation - Singh V.K.; Mukherjee B.; Assa Aravindh S.; Das S. (My University, 2025)
We report the sulfonic acid ([sbnd]SO3H) functionalized two-dimensional (2D) molybdenum disulfide (MoS2) nanosheet with significantly enhanced physical and electrochemical properties as an efficient electrocatalyst for hydrogen evolution reaction (HER). The functionalized 2D-nanosheet shows enhanced electrocatalytic performance than the pristine one. We obtained overpotential as low as ∼82 mV (ƞ10) along with a very low Tafel slope ∼57 mV dec-1 and excellent stability (12 h) in functionalized MoS2. We also found that, with increasing the % of functional group, -SO3H molecules were intercalated through the MoS2 layers resulting in the increase in interlayer spacing from 6.1 Å to 9.4 Å. The intercalated 2D-MoS2 nanosheets with expanded interlayer distance further enhance the surface area, charge-transfer sites, and surface adsorption–desorption by lowering the ΔGH (i.e., the energy barrier of hydrogen adsorption/desorption), thereby accelerating the Volmer step of hydrogen evolution. Finally, density functional theory (DFT) calculations show significant changes in the electronic structure of the functionalized 2D-MoS2 with a considerable shift in the total density of states (DOS) as compared to its pristine counterpart. The DFT calculations reveal that hybridizations occur between the SO3H and p and d states of the S and Mo, which propel the valence band maximum towards higher energies, thus, leading to the narrowing of the bandgap of MoS2. Such changes in electronic properties further reduce work function and facilitate redox-mediated charge-transfer, thereby, enhancing the electrocatalytic activity for HER. © 2022 Elsevier B.V.